Digital Da'wah Strategy of Nahdlatul Ulama Central Java Through the Website Jateng.nu.or.id - Alfin Sirojul Abidin (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The rapid development of digital technology has transformed the practice of Islamic communication, encouraging religious organizations to adopt digital platforms as strategic channels for da'wah activities. While previous studies have predominantly examined digital da'wah through social media platforms and individual religious influencers, limited attention has been given to institutional website-based da'wah strategies implemented by traditional Islamic organizations. This empirical gap is particularly evident in studies of Nahdlatul Ulama (NU) at the regional level. Moreover, existing research often employs a single theoretical perspective, leaving a theoretical gap regarding the integration of multiple communication and media theories in understanding digital religious communication. This study aims to analyze the digital da'wah strategy implemented by Jateng.nu.or.id, the official digital platform of Nahdlatul Ulama Central Java. Employing a qualitative case study approach with thematic analysis, the research draws upon website observations, document analysis, and interviews with key informants involved in digital media management and religious communication. The analysis is informed by Digital Da'wah Theory, Uses and Gratifications Theory, Media Ecology Theory, Diffusion of Innovation Theory, and Social Media Engagement Theory. The findings reveal five strategic dimensions of digital da'wah: institutionalization of digital religious communication, strategic content diversification, multi-platform dissemination, audience engagement and participation, and sustainability through organizational credibility and technological adaptation. The study demonstrates that Jateng.nu.or.id functions not only as a medium for disseminating Islamic teachings but also as a digital ecosystem that strengthens religious authority, community interaction, and public access to credible religious information. Theoretically, this study proposes the Digital Da'wah Ecosystem Strategy Model, offering an integrated framework for understanding institutional digital da'wah in contemporary Muslim societies. Practically, the findings provide insights for Islamic organizations seeking to optimize digital media for sustainable religious communication.